Low cost carriers: the case of Oporto Airport and its touristic impact in the region - Aragão, Catarina Isabel Castanho (2015)
Both Oporto and the North Region of Portugal definitions of tourism have evolved significantly during the past decade. In this journey it is relevant to highlight the contribution of the arrival of Low Cost Carriers (LCCs) at Francisco Sá Carneiro Airport, thus contributing to a rapid expansion of this region as a tourism destination. Hence, this work project aims to understand the touristic and economic impact motivated by the entry of LCCs in Oporto and in the North Region of Portugal and tries to understand if this event was in fact an asset in the development of the aforementioned tourism destinations.